Diversifying into biodiversity - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
'The farmer knows best, and if s/he doesn t know all the options, then let s make more information available' was the message emanating from a workshop on Incentive measures for sustainable use and conservation of Agrobiodiversity held in...